The interaction of focus and phrasing with downstep and post-low-bouncing in Mandarin Chinese - Wang, Bei; Kügler, Frank; Genzel, Susanne (Frontiers in Psychology, 2022)
The current study investigates how focus and phrase boundary affect downstep and post-low-bouncing in Mandarin Chinese (MC). In a production experiment, we systematically manipulated a) the tonal environment by embedding two syllables with either LH tone or HH tone (named as syllable X and Y) sentence-medially in the same carrier sentences containing only H tones; b) strength of the boundary between X and Y by introducing either a syllable boundary or a phonological phrase boundary; and c) information structure by either placing a contrastive focus on syllable X (X-focus), on syllable Y (Y-focus), or on the sentence-final word (Z-focus). A wide-focus condition is served as baseline. Detailed acoustic analysis on F0 and duration showed that: (1) In wide focus and Z-focus conditions, the downstep effect lasted for 3-5 syllables with gradually reduced effect size, hence gradually getting back to the H-tone reference line. (2) When the H tone right after the low tone was focused (Y-focus), on-focus F0 raising did not override downstep. However, the post focus F0 compression (PFC) ended downstep. (3) When the L tone was under focus (X-focus), it caused a post-low-bouncing effect on the following H tones and lasted for about 3 syllables with F0 dropping back gradually. (4) A phrase boundary strengthened downstep (in wide focus condition), but weakened post-low-bouncing. Altogether, it showed that although intonation was largely controlled by informative functions, the physical-articulatory controls were relatively persistent, varied within the pitch range of 3 semitones. Downstep in Mandarin Chinese seems to be a phonetic effect instead of a phonological effect. The gradual tonal F0 change is possibly due to physical constrains, as well as to avoid confusion in informative F0 control.